The roller chain lubricated with ferrofluids. (June 2019) - Zhang, Yanjuan; Yang, Zhengqing; Li, Decai
The sleeve of roller chain periodically squeezes the pin during the process of chain transmission. The lubrication oil located in the gap of the sleeve and pin will be pushed out and cannot be restored automatically. The absence of sufficient lubricating oil can cause friction, wear, and even the roller chain failure between the pin and the sleeve. This article presents a novel method and a new type of chain structure to lubricant roller chain with ferrofluids, which is capable of prolonging the service life of roller chain. The results show that ferrofluids can be remained in the clearance between the sleeve and the pin shaft under the effect of external magnetic field. The ferrofluids that were squeezed out of the clearance can be restored automatically, which ensure the reliability of chain transmission. And the external magnetic field effectively prevents the chain lubrication leakage due to the edge effect of the magnetic field.